Analisis Anteseden Perilaku Manajemen Finansial Pada Generasi Milenial di Indonesia - Aishuia; Kusnul Fitriani; Farah Margaretha Leon (Jurnal Manajemen, 2020)
Millennial generation is identified as materialism, likes credit card promotions, lacks unrealistic knowledge and optimism about the ability to repay debts and has a lifestyle around spending, which follows a "spend now" and "pay later" pattern, and as a consequence, they have a higher tendency towards loan products. The purpose of this study is to determine whether the factors of financial knowledge, behavior of seeking assistance, electronic banking have an influence on the behavior of millennial generation financial management in Indonesia. The sampling method uses convenience sampling. The analysis technique used in this research is Explotary Factor Analysis (EFA) processed using SPSS then Confirmatory Factory Analysis (CFA) and Structural Equation Modeling (SEM) processed using Analysis of Moments Structures (AMOS). The results showed that there was a significant influence on the behavior of seeking assistance and electronic banking on the behavior of millennial generation financial management in Indonesia, otherwise the financial knowledge variable did not affect financial knowledge. This research is useful: for practitioners in the field of finance can take advantage in the utilization of technological aspects (electronic banking) to improve financial management behavior. For financial managers able to focus on various investment and financing decisions, as well as all matters related to it. For investors to reduce the behavior of lack of responsibility in financial management.